If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 2) + -4 + -6x = 3x + 10 Reorder the terms: (2 + X) + -4 + -6x = 3x + 10 Remove parenthesis around (2 + X) 2 + X + -4 + -6x = 3x + 10 Reorder the terms: 2 + -4 + X + -6x = 3x + 10 Combine like terms: 2 + -4 = -2 -2 + X + -6x = 3x + 10 Reorder the terms: -2 + X + -6x = 10 + 3x Solving -2 + X + -6x = 10 + 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + X + 2 + -6x = 10 + 2 + 3x Reorder the terms: -2 + 2 + X + -6x = 10 + 2 + 3x Combine like terms: -2 + 2 = 0 0 + X + -6x = 10 + 2 + 3x X + -6x = 10 + 2 + 3x Combine like terms: 10 + 2 = 12 X + -6x = 12 + 3x Add '6x' to each side of the equation. X + -6x + 6x = 12 + 3x + 6x Combine like terms: -6x + 6x = 0 X + 0 = 12 + 3x + 6x X = 12 + 3x + 6x Combine like terms: 3x + 6x = 9x X = 12 + 9x Simplifying X = 12 + 9x
| 91=-7(7-4k) | | 14=z-y | | -5n-7=23 | | Cosx=2sinx | | -6-6x=1x+4 | | 14a^2+7a-196=0 | | 355=-5n-5(8n-8) | | 2cos^2x+5sinx-5=0 | | 1/9=?/45 | | (X+2)-2(4-3x)=2(x+4)-4 | | (-7)-x=-5 | | 9n^2+94n-168=0 | | 7x-8=55-2x | | (-3)-x=2 | | p-12=218 | | .5x^2=8 | | -6a=36a | | y=2x-5x+7 | | 2.9r=-5.7t-5 | | x-(-14)=-11 | | 5y-9=7+y | | 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 | | 3x+9x+5=17 | | 4-5p=8 | | 2(X+8)+5x-9=3(X+2)+4(2x+9)-5(3x+8)+25-12x | | 3x^2=89 | | 5v^2-8v-21=0 | | 10y-21=7y | | 4b+7=15 | | 7x+11=x-2510 |